A dynamic replication strategy based on exponential growth/decay rate - Madi, Mohammed; Hassan, Suhaidi; Yusof, Yuhanis (2009)
Data Grid is an infrastructure that manages huge amount of data files, and provides intensive computational resources across geographically distributed collaboration.To increase resource availability and to ease resource sharing in such environment, there is a need for replication services.Data replication is one of the methods used to improve the performance of data access in distributed systems.In this paper, we include issues arising in data replication domain and also we propose a dynamic replication strategy that is based on exponential growth or decay rate. The purpose of the proposed strategy is to identify which files to be replicated.This is achieved by estimating number of accessed of a file in the upcoming time interval.The greater the value, the more popular the file is and therefore will be selected to be replicate.